COPING STRATEGY IN MOTHER WHO HAVE POST PARTUM BLUES SYNDROME DI WILAYAH KOTA KEDIRI - Anna Septina Andarini; Zuhrotun Ulya (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
The postpartum blues occurs when a mother fails to accept her condition caused by pregnancy, pregnancy, childbirth and post partum. This research is very important because postpartum blues which is known as a form of mild depression can develop into postpartum depression if not treated properly. This study aims to explore coping strategies for postpartum blues sufferers by using a qualitative research method with a case study method. Two participants who were selected by purposive sampling technique, who experienced the postpartum blues were obtained from the city of Kediri. Methods Data collection was carried out through interviews (in-depth interviews), field notes, and input from The Edinburgh Postnatal Depression Scale (EPDS). The results of this study indicate that the coping used in mothers who experience post partum blues uses problem focused coping, but the participants have also used emotional focused coping. The use of this coping variation does not indicate that the strategy taken is decided without any consideration of problem solving. There are variations in the use of coping strategies because coping strategies do not have to end in solving the problem at once. This problem makes the participant's condition better than before. The participants feel calmer in dealing with every problem, are confident, and will stimulate the participants to seek more knowledge and be able to provide support to anyone, especially for mothers who experience post partum blues.Keywords: coping Strategy, postpartum blues